1989
DOI: 10.1111/j.1600-0765.1989.tb01789.x
|View full text |Cite
|
Sign up to set email alerts
|

Collagen membranes prevent apical migration of epithelium and support new connective tissue attachment during periodontal wound healing in dogs

Abstract: The capacity of collagen membranes to prevent the apical migration of epithelium and to support new connective tissue attachment was assessed in experimental periodontal defects in dogs. Experimental periodontal defects were produced in 8 mongrel dogs by removing the alveolar bone and the periodontal ligament over the most coronal 5 mm of the labial aspect of the maxillary canines. Experimental defects associated with the right canine and its surrounding bone were covered by collagen membranes prepared by air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
4

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 11 publications
2
51
0
4
Order By: Relevance
“…Both resorbable and non-resorbable membranes have been used for these applications with comparable success, although a key advantage in the use of resorbable materials is that the need for re-entry into the regenerated site is eliminated [35,36]. Membranes derived from natural compounds (i.e., collagen) are degraded by an enzymatic process (biodegradation), catalysed by cells in the local microenvironment and within the developing tissue [37,38], but synthetic polymers (i.e., derivatives of polylactic and polyglycolic acid) are hydrolysed (bioabsorption) into the natural metabolites lactic acid and glycolic acid [39,40]. The polylactic scaffolds are popularly employed due to familiarity with their favourable biocompatible properties, which helps minimise an undesirable inflammatory response.…”
Section: Approaches For Growth Factor Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Both resorbable and non-resorbable membranes have been used for these applications with comparable success, although a key advantage in the use of resorbable materials is that the need for re-entry into the regenerated site is eliminated [35,36]. Membranes derived from natural compounds (i.e., collagen) are degraded by an enzymatic process (biodegradation), catalysed by cells in the local microenvironment and within the developing tissue [37,38], but synthetic polymers (i.e., derivatives of polylactic and polyglycolic acid) are hydrolysed (bioabsorption) into the natural metabolites lactic acid and glycolic acid [39,40]. The polylactic scaffolds are popularly employed due to familiarity with their favourable biocompatible properties, which helps minimise an undesirable inflammatory response.…”
Section: Approaches For Growth Factor Deliverymentioning
confidence: 99%
“…Two common types of polymeric materials used in growth factor delivery strategies are natural collagen-derived materials [37,38,51] and synthetic polymers of lactic and glycolic acid (i.e., poly[lactide-co-glycolide]) [40,52]. Extracellular matrix-derived macromolecules such as collagen have been used for many years in biomaterial application [53], and it is now possible to create artificial analogues of extracellular matrix proteins using recombinant DNA technology [54].…”
Section: Approaches For Growth Factor Deliverymentioning
confidence: 99%
“…Even though studies on GTR have evidenced formation of new attachment connective tissue, deposition of new cementum, new periodontal ligament and new bone formation in surgically created defects submitted to GTR with resorbable membrane barriers 15 , some studies reported the non-formation of new bone 16 and detected dense connective tissue instead of alveolar bone 8 after application of barriers in surgically created defects in animals. In those situations, the clinical repair of bone defects cannot be defined as regeneration, even when there is formation of new attachment connective tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The favorable biological characteristics of collagen has led to investigations on its clinical application in procedures related to periodontal regeneration. Several studies (Pitaru, 1987(Pitaru, , 1989YafTe, 1987) reported utilizing various forms of type I collagen as a membrane barrier for guided tissue regeneration procedures. Clinical human studies (Chung et al, 1990;Anderson, 1991) have also demonstrated positive results with type I collagen membranes in the treatment of periodontal defects using guided tissue regeneration techniques.…”
Section: Extracellular Matrix In Clinical Applicationmentioning
confidence: 98%